2014
DOI: 10.1080/0889311x.2014.886202
|View full text |Cite
|
Sign up to set email alerts
|

Neutron powder diffraction – new opportunities in hydrogen location in molecular and materials structure

Abstract: The potential of neutron powder diffraction in the location of hydrogen atoms in molecular materials and inorganic-molecular complexes is reviewed. Advances in instrumentation and data collection techniques that have made this field accessible are reviewed, along with a wide range of applications carried out by our collaboration investigating functional materials, hydrogen-containing minerals and molecular compounds. Some of the limitations in this area, particularly for molecular systems, are also addressed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 91 publications
0
3
0
Order By: Relevance
“…Given that complete removal of excess DMF and Me-bdc was not possible without structural degradation, there is considerable incoherent scattering due to hydrogen. However, Weller et al, 70,71 as well as our previous MOF work, 72 have shown that neutron powder diffraction is quite possible with various amounts of hydrogen in crystalline materials, with hydrogen positions readily accessible due to their negative contrast. It is understandable that due to the amount of hydrogen, as well as the large unit cell, the patterns do not contain much information beyond Q = 2 Å −1 , despite containing sharp crystalline peaks.…”
Section: ■ Experimental Sectionmentioning
confidence: 86%
“…Given that complete removal of excess DMF and Me-bdc was not possible without structural degradation, there is considerable incoherent scattering due to hydrogen. However, Weller et al, 70,71 as well as our previous MOF work, 72 have shown that neutron powder diffraction is quite possible with various amounts of hydrogen in crystalline materials, with hydrogen positions readily accessible due to their negative contrast. It is understandable that due to the amount of hydrogen, as well as the large unit cell, the patterns do not contain much information beyond Q = 2 Å −1 , despite containing sharp crystalline peaks.…”
Section: ■ Experimental Sectionmentioning
confidence: 86%
“…These yield data with low diffraction peak intensities on very large backgrounds requiring very long data collection times and, generally, yielding structural models with lower precision. Neutron source and instrument developments have resulted in new possibilities to study hydrogenous materials without the requirement, cost and associated problems to deuterate, [44][45][46] while also offering relatively short counting times 47 and prospects to take advantage of the scattering length contrast of H cf. D (−3.739 fm and 6.671 fm respectively).…”
Section: Discussionmentioning
confidence: 99%
“…[41] Neutron powder diffraction, still a relatively new method, has emerged as a valuable tool for investigations of phase transitions at high pressures. [42][43][44] …”
Section: Neutron Diffraction: Locating the Hydrogen Atomsmentioning
confidence: 98%